An enigmatic frog of the genus Atelopus (Family Bufonidae) from Parque Nacional Chirripó, Cordillera de Talamanca, Costa Rica - Savage, Jay M. (2009)
A distinctive new species of Atelopus is described from Parque Nacional Chirripó Grande, Cordillera de Talamanca (3 400-3 500 m). It closely resembles populations of the Atelopus ignescens complex from the Andes of northern Ecuador and southern Colombia. It differs most significantly from these frogs in the pattern of spiculae and coni development on the throat, chest, hands and feet. The Costa Rican species appears to be an outlier of the complex inexplicably separated geographically from its nearest allies by an over land distance of about 1 600 km.